High reactivity and bactericidal effects of plasma‐activated mist from hydrogen peroxide solution. Issue 1 (13th October 2022) - Zhou, Yangyang; Jiang, Tao; Zhang, Li; Wang, Sen; Zhou, Renwu; Cui, Xinglei; Fang, Zhi
Abstract: Hydrogen peroxide solutions are often utilized in logistics sterilization by misting, although their sterilizing capacity is diminished. To meet the high‐efficient and long‐term sterilization requirements of logistics, the reactivity and bactericidal efficiency are improved with plasma‐activated H2 O2 solutions mist (PAHM). PAHM promotes an approximately double increase in the concentration of reactive nitrogen species, four times increase in the O3 concentration, and 36.2 times increase in H2 O2 compared with water mist activation. Escherichia coli and Staphylococcus aureus are selected as the model microorganisms to evaluate the bactericidal activity. Results show that PAHM can reduce the numbers of both bacteria by two orders of magnitude after 3 min of treatment, similar to inactivated H2 O2 for 10 min of treatment. Abstract : Plasma activation is an effective method to enhance the bactericidal effect, yet little is known about the activation of H2 O2 mist, which is widely employed in logistics sterilization. To obtain the mechanisms related to the enhancement of the reactivity and sterilization efficiency, this study presented a comparative analysis of reactive substances and bactericidal effects for plasma‐activated air, plasma‐activated water mist, and plasma‐activated H2 O2 solution mist.